2005
DOI: 10.1128/mcb.25.13.5492-5498.2005
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Insertion by Anthrax Protective Antigen in Cultured Cells

Abstract: The enzymatic moieties of anthrax toxin enter the cytosol of mammalian cells via a pore in the endosomal membrane formed by the protective antigen (PA) moiety. Pore formation involves an acidic pH-induced conformational rearrangement of a heptameric precursor (the prepore), in which the seven 2␤2-2␤3 loops interact to generate a 14-strand transmembrane ␤-barrel. To investigate this model in vivo, we labeled PA with the fluorophore 7-nitrobenz-2-oxa-1,3-diazole (NBD) at cysteine residues introduced into the 2␤2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The insertion half-time was on the order of several seconds, as measured by K ϩ release or enhancement of fluorescence of NBD at position 305 and was much more rapid than that observed with unbound PA. Thus the insertion was largely complete before the complex could proceed down the pathway to inactivation (if such a pathway is in fact operative with membrane-bound PA.) Consistent with observations in other systems, the binding to His-R2 shifted the pH threshold of conversion to the pore to a lower range (9,13,37); mutations in PA known to affect heptamerization or prepore-to-pore conversion inhibited pore formation in the predicted way (3,25); and membrane insertion by a fluorescently tagged form of PA gave results consistent with prior findings in cells and with the ␤-barrel model of pore formation (21). Also, binding of LF N -DTA was shown to depend on proteolytic activation of PA (3).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The insertion half-time was on the order of several seconds, as measured by K ϩ release or enhancement of fluorescence of NBD at position 305 and was much more rapid than that observed with unbound PA. Thus the insertion was largely complete before the complex could proceed down the pathway to inactivation (if such a pathway is in fact operative with membrane-bound PA.) Consistent with observations in other systems, the binding to His-R2 shifted the pH threshold of conversion to the pore to a lower range (9,13,37); mutations in PA known to affect heptamerization or prepore-to-pore conversion inhibited pore formation in the predicted way (3,25); and membrane insertion by a fluorescently tagged form of PA gave results consistent with prior findings in cells and with the ␤-barrel model of pore formation (21). Also, binding of LF N -DTA was shown to depend on proteolytic activation of PA (3).…”
Section: Discussionsupporting
confidence: 87%
“…The intensity of NBD fluorescence at 544 nm increased upon a shift from a polar to a non-polar environment, and earlier we monitored insertion of various residues of the 14-strand ␤-barrel into membranes of Chinese hamster ovary-K1 cells after replacing those residues with Cys and reacting the protein with a thiol-reactive form of NBD (21). In that study, NBD attached to an introduced Cys at position 305 (facing the lipid bilayer) showed a strong increase in fluorescence, whereas at position 306 (facing the aqueous lumen) the fluorophore showed little change.…”
Section: Figure 4 His-r2-dependent Kmentioning
confidence: 98%
See 1 more Smart Citation
“…R2 LF N-DTA and prepore were prepared as described in ref. 26. Protein concentrations were determined by spectrophotometry (A 280) and densitometry on SDS/PAGE with BSA as standard.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting toxic complexes are internalized, and the low pH within the endosome promotes a conformational change in the prepore moiety that allows it to insert into endosomal membranes and form a pore. The conformational transition of the prepore to the pore depends on the association of the 2␤2-2␤3 loops of the seven PA63 subunits to form a membrane-spanning, 14-stranded ␤ barrel (1,21,22).…”
mentioning
confidence: 99%